Fatty Acid use in Diving Mammals: More than Merely Fuel - Trumble, Stephen J.; Kanatous, Shane B. (Frontiers in Physiology, 2012)
Diving mammals, are under extreme pressure to conserve oxygen as well as produce adequate energy through aerobic pathways during breath-hold diving. Typically a major source of energy, lipids participate in structural and regulatory roles and have an important influence on the physiological functions of an organism. At the stochiometric level, the metabolism of PUFAs (polyunsaturated fatty acids) utilizes less oxygen than metabolizing either MUFAs (monounsaturated fatty acids) or SFAs (saturated fatty acids) and yields fewer ATP per same length fatty acid. However, there is evidence that indicates the cellular metabolic rate is directly correlated to the lipid composition of the membranes such that the greater the PUFA concentration in the membranes the greater the metabolic rate. These findings appear to be incompatible with diving mammals that ingest and metabolize high levels of unsaturated fatty acids while relying on stored oxygen. Growing evidence from birds to mammals including recent evidence in Weddell seals also indicates that at the whole animal level the utilization of PUFAs to fuel their metabolism actually conserves oxygen. In this paper, we make an initial attempt to ascertain the beneficial adaptations or limitations of lipids constituents and potential trade-offs in diving mammals. We discuss how changes in Antarctic climate are predicted to have numerous different environmental effects; such potential shifts in the availability of certain prey species or even changes in the lipid composition (increased SFA) of numerous fish species with increasing water temperatures and how this may impact the diving ability of Weddell seals.